Tinjauan Maqāṣid Al-Syarī'ah terhadap Fenomena Penundaan Pernikahan (Late Marriage) di Kalangan Generasi Muda Singapura - Zuraimi Bin Abdul Basheer; Rizki Muhammad Haris (Bahasa Indonesia, 2026)
The trend of Late Marriage among Singapore's younger generation has increased consistently over the past two decades, as reflected in the rising median age at first marriage and the decline in fertility rates to below replacement level. This phenomenon raises important questions regarding its compatibility with the objectives of Maqāṣid al-Sharīʿah, particularly the preservation of lineage (ḥifẓ al-nasl). This study aims to identify the factors contributing to Late Marriage in Singapore, analyze its implications for individuals and society, and evaluate the phenomenon through a hierarchical Maqāṣid al-Sharīʿah framework. The research employs a qualitative descriptive-analytical approach using a library research design and document analysis. Secondary data were obtained from official sources, including the Singapore Department of Statistics, the Institute of Policy Studies, and the National Youth Council, and were triangulated with previous academic literature as well as classical and contemporary Islamic jurisprudential sources. The findings identify four principal factors contributing to Late Marriage: financial constraints, career and educational priorities, concerns about divorce, and difficulties in finding a compatible partner (marriage squeeze). From the perspective of Maqāṣid al-Sharīʿah, postponing marriage based on personal readiness (ahliyyah) can be considered religiously justifiable. However, prolonged postponement driven by structural pressures may weaken the objective of preserving lineage (ḥifẓ al-nasl) at the societal level. The study recommends a collaborative approach involving government policies, religious institutions, and community organizations to support young adults' readiness for marriage while respecting their financial and emotional preparedness. It also highlights the need for future empirical research to strengthen these conceptual findings through primary data